2008
DOI: 10.1017/s1431927608080069
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Cholesterol Accumulation Inhibits Subsequent Hydrolysis of Lipoprotein Cholesteryl Ester

Abstract: Human macrophages incubated for prolonged periods with mildly oxidized LDL (oxLDL) or cholesteryl ester-rich lipid dispersions (DISP) accumulate free and esterified cholesterol within large, swollen lysosomes similar to those in foam cells of atherosclerosis. The cholesteryl ester (CE) accumulation is, in part, the result of inhibition of lysosomal hydrolysis due to increased lysosomal pH mediated by excessive lysosomal free cholesterol (FC). To determine if the inhibition of hydrolysis was long lived and furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 48 publications
6
49
1
Order By: Relevance
“…Jerome et al (38) have demonstrated that oxidized LDL accumulation within lysosomes inhibits subsequent lipoprotein hydrolysis and that lipid-engorged lysosomes failed to maintain an acidic pH. We proposed that the Hp genotype-dependent oxidative effect on LDL accumulated within lysosomes may further increase its pH leading to more lysosomal dysfunction.…”
Section: Demonstration That the Increased Oxidative Stress In Lysosommentioning
confidence: 82%
“…Jerome et al (38) have demonstrated that oxidized LDL accumulation within lysosomes inhibits subsequent lipoprotein hydrolysis and that lipid-engorged lysosomes failed to maintain an acidic pH. We proposed that the Hp genotype-dependent oxidative effect on LDL accumulated within lysosomes may further increase its pH leading to more lysosomal dysfunction.…”
Section: Demonstration That the Increased Oxidative Stress In Lysosommentioning
confidence: 82%
“…by guest, on March 24, 2019 www.jlr.org Downloaded from particles, including oxidized LDL, aggLDL, and CE-DISP is, in large part, the result of inhibition of lysosomal CE hydrolysis in response to an initial accumulation of excess FC within the lysosome ( 45,50,51 ). Lysosomal CE hydrolysis is a key rate-limiting step in the cellular clearance of exogenously derived sterol.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, TG can prevent subsequent cellular cholesterol accumulation and can mobilize preexisting stores of cellular CE, including the large volume of sterol that accumulates in cellular lysosomes ( 50 ). This is in stark contrast to direct stimulation of extralysosomal cholesterol mobilization, which does not affect the cholesterol trapped within lysosomes ( 16,51 ).…”
Section: Resultsmentioning
confidence: 99%
“…Aliquots were stored at −80°C for lipid/chemical determinations while the HDL fraction (d = 1.063 to 1.22 g/ml) was isolated from fresh plasma by density gradient ultracentrifugation (DGUC). 23 Because of their size and small volume, we were initially concerned that the DGUR method would yield insufficient HDL fraction and began the studies using samples (three from each group) obtained by precipitating the apoB fraction with polyethylene glycol (PEG) solution as described. 24 HDL isolation method did not influence results of migration and cytokine expression studies and results were combined.…”
Section: Methodsmentioning
confidence: 99%